Pertanggungjawaban Bank Dalam Perkara Tindak Pidana Pencucian Uang Yang Tidak Menjalankan Prinsip Kehati-Hatian Bank - Istiqomah (2020)
Money Laundering Crime is also known in money laundry terms. is a process whereby the assets of the perpetrator, especially cash assets obtained from a criminal act, are manipulated in such a way that the assets appear to come from legitimate sources. Banks as financial service providers become the target and means to commit crimes including money laundering. The prudential principle of bank, one of which aims to prevent banks from becoming a media for money laundering, derived from the prudential principles is the know your customer principle that must be applied by banks, activities in the form of identifying prospective customers and monitoring the characteristics of each customer transaction, and reporting if there are suspicious transactions in accordance with statutory regulations. This thesis tries to analyze the bank's prudential principles and the know your customer principle that developed into customer due diligence (CDD) and enhanced due diligence (EDD), which should be carried out by banks as an effort to prevent the crime of money laundering related to the case of the former Bangkalan regent Fuad Amin is entangled in a money laundering case, the mode is by putting money from the proceeds of corruption to several banks with several different identities. This should not be allowed, because when a prospective customer will register as a customer in a bank, he must provide a true identity that is equipped with supporting documents, therefore the importance of the principle of knowing customers can be a benchmark for banks in money laundering. Then how is the responsibility of the bank as a corporation participating in the crime of money laundering carried out by ignoring the precautionary principle and the principle of getting to know customers in accordance with relevant laws and regulations.